Short Range Order Evolution in the Preparation of SnO2 Based Materials - Brito, G. E S [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Briois, V.; Dexpert-Ghys, J.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Springer Nature, 1997)
The evolution of Eu3+ doped SnO2 xerogels to the cassiterite structure observed during sintering was studied by means of Eu3+ spectroscopy, XRD and EXAFS at the Sn K-edge. Eu3+ ions adsorbed at the surface of colloidal particles present a broad distribution of sites, typical of oxide glasses. With sintering at 300°C, this distribution is still broadened. Crystallization is clearly observed by the three techniques with increasing sintering temperature. It is found that the addition of Eu3+ limits the crystallite growth.
Keywords: Eu3+ spectroscopy; EXAFS; Sintering; SnO2 xerogel; XRD; Adsorption; Composition effects; Crystal growth; Crystallization; Doping (additives); Europium; Particles (particulate matter); Spectroscopic analysis; Thermal effects; Tin compounds; X ray diffraction analysis; Extended X ray absorption fine structures (EXAFS); Xerogels; Gels